59.3k views
3 votes
Solve the system by elimination

Solve the system by elimination-example-1
User Tim Moore
by
5.5k points

1 Answer

7 votes

First of all we will eliminate x from our equations. In order to do that we will use our first and second equation and then we will use second and third equation.


-2x+2y+3z=0...(1)\\-2x-y+z=-3....(2)

Upon subtracting 2 equation from 1 we will get,


3y+2z=3....(4)

Now we will use second and third equation to eliminate x.


-2x-y+z=-3....(2)\\2x+3y+3z=5....(3)

Adding 2nd and 3rd equation we will get,


2y+4z=2....(5)

Now we will find out y from our 4th and 5th equation.


2*(3y+2z)=2*3....(4)\\2y+4z=2....(5)

Upon subtracting 5th equation from 4th equation we will get,


4y=4\\y=1

Now let us find out z by substituting y's value in 5th equation.


2*1+4z=2\\4z=2-2\\z=0

Now we will find x from by substituting y and z's value in equation 1.


-2x+2*1+3*0=0\\-2x+2=0\\2=2x\\x=1

Therefore, x=1, y=1 and z=0 is the solution of the given system.

User TelJanini
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.